Scaling of Laser Fusion Experiments for DD-Neutron Yield - Krása, Josef; Klír, Daniel (Frontiers in Physics, 2020)
Yields of neutrons produced in various laser fusion experiments conducted in recent decades are compared with each other. It has surprisingly been found that there is a possibility to make an overall elucidation of the variance in the number of neutrons produced in the various experiments. The common method is based on definition of the energy conversion efficiency as a ratio between the energy carried out by neutrons produced through the fusion reaction and the input energy given by laser energy, E, focused on a target. The neutron-yield – laser-energy diagram is the basic chart used to interpret the spread of experimental data in terms of the experimental efficiency of the laser-matter interaction. Experiments carried out using a single laser system show that laser energy dependence of the yield can be well characterized by a power law, Y = QE^a, where Q is the parameter reflecting possible dependence on the pulse duration, laser intensity, laser contrast ratio, focal geometry, target structure, etc. Sorting the values of the neutron yields obtained in various experiments shows that the power law Y=QE^1.65 is suitable to determine lines in the Y-E diagram each of them, where the value of Q is associated with quality of experimental conditions. This sorting shows the order-of-magnitude differences in yields found in various experiments, which can be characterized by the value of the parameter Q. Due to the easy feasibility and the large number of DD fusion experiments performed, the overall Y-E diagram gives a chance to identify suitable laser systems for effective DD fusion experiments. It can, therefore, be assumed that some of the conclusions of these experiments could also be applied to the experimental arrangement suitable for optimizing p11B fusion.